TRADE UNIONS FOR THE SELF-EMPLOYED AND PLATFORM WORKERS: EXPERIENCE OF RUSSIA AND FOREIGN COUNTRIES - MIRONOVA S.M.; LITVINENKO Z.G. (Legal Bulletin)
In the context of the gig economy, platform economy, digitalization of all processes, the structure of employment is changing and the forms of labor relations are changing, nonstandard forms of employment are emerging, and instead of concluding employment contracts with employees, companies prefer to enter into civil contracts. Forms of employment such as self-employment and platform employment are emerging. The position of such workers is less protected in terms of their rights and the guarantees provided to them. There is a need to ensure the rights of workers employed in self-employment or platform employment. And one of these tools could be their support from trade unions. The purpose of the study is to familiarize ourselves with the experience of Russia and a number of foreign countries in the regulation and practice of legal protection of collective rights of self-employed and platform workers through trade unions. The research materials included regulations, judicial practice, statistical data, as well as data from trade unions of a number of foreign countries (Germany, Spain, Great Britain) and the Russian Federation. The comparative legal method and methods of formal logic (analysis, synthesis, generalization, induction, deduction, etc.) were chosen as the main research methods. At this stage of development of platform employment and the work of self-employed citizens, it is necessary to resolve issues related to the protection of their rights through trade unions, the introduction of collective bargaining and the conclusion of collective agreements between such workers and the digital platforms through which they work. Platform workers and self-employed people are the weaker side in interaction with the platform, since, as a rule, they are forced to agree to those conditions for the provision of services / performance of work that are less profitable for them, and often even enslaving. Practice shows that while the legal status of “independent contractors” is not fully regulated, their ability to protect their rights through a trade union is not always supported in court, which also requires regulatory establishment. Such interaction between trade unions, platforms and their workers with non-standard forms of employment requires its legal regulation and enshrinement in national employment legislation, and appropriate changes to the legislation on trade unions.